Identification of Fishing Gear in Java from Historical and Cultural Perspective - Sri Indrahti; Siti Maziyah (Diponegoro University, 2021)
Fishing is one of the livelihoods in Java which causes the emergence of different fishing gears from one place to another. By applying a historical perspective, this paper identifies variety of fishing gears for fishermen in Jepara and Pekalongan which can be traced to their historical roots since prehistoric times. Two important questions raised in this article, among others, related to the history of fishing gear for fishermen in Java and why this fishing gear is still sustainable up to the present day. This research was conducted in several stages. First, it begins by searching for various fishing gears based on literature studies. Second, field research which conducted in Jepara and Pekalongan to determine the continuity of culture related to the findings of fishermen's fishing gear. The results showed that fishing is a job that has been done by humans for a long time. The variety of fishing gear used are adjusted to the natural conditions where the fish are located. The diversity of fishing gear shows that fishing activity can be used either as a side job or a main job. Even though it has passed a dozen centuries, it turns out that some traditional fishing gear are still used until today, indeed with modifications and innovations.